New experimental zirconia-reinforced rice husk nanohybrid composite and the outcome of its surface roughness and microhardness in comparison with commercialized nanofilled and microhybrid composite resins - Galvin Sim Siang Lin; Nik Rozainah Nik Abdul Ghani; Noor Huda Ismail; Kiran Singbal; Tahir Yusuf Noorani; Noraida Mamat (Wolters Kluwer Medknow Publications, 2021)
Background: An ideal composite resin should demonstrate smooth surface after polishing and high hardness value to provide long-term success. Thus, this study aimed to compare the surface roughness and microhardness of new experimental zirconia-reinforced rice husk nanohybrid composite (Zr-Hybrid) with commercialized nanofilled (Filtek-Z350-XT) and microhybrid composite (Zmack-Comp) resins before and after artificial ageing. Methods: One hundred and eighty standardized disc samples were prepared, of which ninety samples each were used for surface roughness and microhardness test, respectively. They were divided equally into: Group 1 (Filtek-Z350-XT), Group 2 (Zmack-Comp), and Group 3 (Zr-Hybrid). For surface roughness test, all samples were polished with aluminium oxide discs and further subdivided into aged and unaged subgroups, in which composite samples in aged subgroups were subjected to 2500 thermal cycles. Next, all the samples were subjected to surface roughness test using a contact stylus profilometer. As for microhardness test, all the aged and unaged samples were tested using a Vickers hardness machine with a load of 300 kgf for 10 s and viewed under a digital microscope to obtain microhardness value. Data were analyzed using two-way ANOVA followed by post hoc Tukey's honestly significant difference and paired sample t-test with significance level set at P = 0.05. Results: In both the aged and unaged groups, Zr-Hybrid showed statistically significantly lower surface roughness (P < 0.05) than Filtek-Z350-XT and Zmack-Comp, but no statistically significant difference was noted between Filtek-Z350-XT and Zmack-Comp (P > 0.05). A similar pattern was noted in microhardness test, whereby Zr-Hybrid showed the highest value (P < 0.05) followed by Filtek-Z350-XT and lastly Zmack-Comp. Besides, significant differences in surface roughness and microhardness were noted between the aged and unaged groups. Conclusion: Zr-Hybrid seems to demonstrate better surface roughness and microhardness value before and after artificial ageing.